Political Dynasties in the Philippine Congress - Mendoza, Ronald U (Archīum Ateneo, 2019)
The relationship between democracy and inclusive growth is rather complicated. On the one hand, democracies are built with mechanisms and processes to enable the state to respond to the needs of its citizenry. It can be argued that this setup could lead to greater investments in human capital and equitable socioeconomic outcomes. On the other hand, democracies are vulnerable to policy paralysis and myopia. For instance, insecure tenures and term limits make it challenging to reconcile short-term aspirations and personal interests with the pursuit of reforms essential for the promotion of inclusive growth…